2008
DOI: 10.1179/096992608x297003
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and suffering of patients with heart failure

Abstract: 2008) Spirituality and suffering of patients with heart failure, Progress in Palliative Care, 16:5-6, 257-265 To link to this article: http://dx.Heart failure is the terminal stage of cardiac disease and, as such, potentially involves spiritual issues and suffering. Spirituality has been shown to be related to adaptation, life satisfaction, and depression. Further, as depression is an independent predictor of mortality in patients with heart failure, spirituality is important for clinicians to consider. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Life review has also been suggested as a potential intervention (K. Y. Chan, Lau, et al, 2016; Oates, 2004; Steinhauser et al, 2008; Westlake, Dyo, Vollman, & Heywood, 2008). This intervention is targeted at helping individuals work through the meaning-making process to achieve a positive view of past and present life events (Steinhauser et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Life review has also been suggested as a potential intervention (K. Y. Chan, Lau, et al, 2016; Oates, 2004; Steinhauser et al, 2008; Westlake, Dyo, Vollman, & Heywood, 2008). This intervention is targeted at helping individuals work through the meaning-making process to achieve a positive view of past and present life events (Steinhauser et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…() and highlights the potential value of pastoral counselling (Westlake et al . ) in enhancing spiritual wellbeing and in reducing depression (Whelan‐Gales et al . ).…”
Section: Experience Of Healthcare and Effects Of The Illnessmentioning
confidence: 99%
“…) and interventions such as meaning‐centred therapies and pastoral counselling (Westlake et al . ). Few studies, however, have focused on exploring the spiritual needs and spiritual support preferences of heart failure patients in the UK.…”
Section: Introductionmentioning
confidence: 97%
“…There is a preponderance of evidence indicating that HF exacts a tremendous physical, psychological, emotional and spiritual toll on the people diagnosed with it 28 and the family members who care for them. 2, 9, 10 Multiple research teams have examined the experience of patients with late-stage HF.…”
mentioning
confidence: 99%